2011
DOI: 10.5143/jesk.2011.30.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Human Error in Shipbuilding Industry

Abstract: The nuclear power plants and chemical industries are trying to find human error to prevent occupational injury. The ratio of occupational injury is higher than the other industries in shipbuilding industry. It is known that the most important reason is human error. Recently, the shipbuilding industries interest in human error to prevent occupational injury. This paper outlines four approaches of human error identification used in shipbuilding industry such as survey of occupational injury, root cause analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Wickens et al [25] divided human error into three types according to human information processing [26]. The aforementioned errors can occur not only in the process of manually constructing the geometry database but also in most office work.…”
Section: Human Error Occurring During Manual Calculationmentioning
confidence: 99%
“…Wickens et al [25] divided human error into three types according to human information processing [26]. The aforementioned errors can occur not only in the process of manually constructing the geometry database but also in most office work.…”
Section: Human Error Occurring During Manual Calculationmentioning
confidence: 99%
“…Thus necessity of researches aiming to reduce workplace safety accident has been raised. In regard to the number of industrial accident victims, Korea shipbuilding had demonstrated the significant rise in 2003, showed slowdown trend from 2004, yet has presented increase trend again lately since 2008 [1] [2]. Korea Occupational Safety and Health Agency showed that averagely 40 workers lost their lives in shipbuilding yards every year (45 in 2008) as the industry involves numerous outdoor and heavyweight works unlike general manufacturing and has a working environment which mainly requires mobile equipment.…”
Section: Introductionmentioning
confidence: 99%
“…따라서 본 연구에서는 이러한 문제점을 개선하기 위해 휴먼에러 이론을 분석하고, 스마트 기능이 추가된 휴먼에러 방지용 MCC 제어시스템의 제안을 통해 전기설비 휴먼에러 사고를 최소화하는 데 목적이 있다. (Kim et al, 2011). 첫 번째, 정보처리 과정에서 휴먼에러의 경우 Table 2와 같이 정보처리 단계의 인지, 판단(의사결정), 동작, 확인 등의 과정에서 발생한다고 하였다 (Lim and Lee, 2012;Wickens et al, 2004).…”
unclassified